Lithium battery ternary material with low residual alkali content and preparation method thereof

By sintering nickel, cobalt, manganese ternary material in the kiln and performing secondary coating treatment, the problem of high residual alkali content in ternary lithium batteries is solved, reducing internal resistance and improving battery performance.

CN119160950APending Publication Date: 2024-12-20CHANGSHU INSTITUTE OF TECHNOLOGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411306102.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-19
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

The high residual alkali content in existing ternary lithium batteries leads to high internal resistance, affecting battery performance.

Method used

By mixing the precursor of the nickel-cobalt-manganese ternary positive electrode material with lithium carbonate in a certain proportion and sintering in the kiln, the intake air volume, intake pressure and the kiln furnace pressure are reduced in sequence from the cooling section to the heating section. Process, combining secondary or tertiary coating to prepare ternary materials of low residual alkali lithium batteries.

Benefits of technology

It effectively reduces the residual alkali content of lithium batteries, reduces the accumulation of waste gas inside the kiln, reduces production power consumption, and improves the cycle retention rate and discharge capacity of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119160950A_ABST
    Figure CN119160950A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a lithium battery ternary material with low residual alkali content, and the preparation method comprises the following steps: S1, a nickel-cobalt-manganese ternary positive electrode material precursor and lithium carbonate are mixed according to a certain proportion to form a uniformly dispersed material, the chemical formula of the nickel-cobalt-manganese ternary positive electrode material precursor is Ni < x > Co < y > Mn < z > (OH) < 2 >, and x + y + z = 1; s2, feeding the mixed materials in the step S1 into a kiln, and sintering according to an air intake and exhaust process that the air intake amount, the air intake pressure and the furnace pressure of the kiln are sequentially reduced from a cooling section, a constant temperature section to a heating section in the kiln; and S3, crushing the sintered material in the step S2, mixing the crushed material with an additive, and carrying out secondary or tertiary coating sintering to prepare the lithium battery ternary material with low residual alkali content. The ternary material prepared by the method has the characteristics of low residual alkali amount, high yield and low energy consumption, and is suitable for industrial continuous production, and the preparation method is suitable for large-bowl-loading-amount production, so that the production unit consumption is further reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lithium battery positive electrode material preparation, and relates to a low residual alkali lithium battery ternary material and a preparation method thereof. Background Art

[0002] Electric vehicles have gradually become the largest demand industry for lithium batteries. With the global greenhouse effect becoming increasingly significant, all countries have increased their attention to renewable resources. People's demand for lithium batteries will continue to grow, and the lithium battery industry has a good development prospect.

[0003] In the existing battery system, lithium iron phosphate and ternary NCM / NCA dominate the positive electrode materials of power batteries. For safety and low cost considerations, lithium iron phosphate batteries are mainly used in new energy commercial vehicles and energy storage fields; in the field of new energy passenger vehicles, users' anxiety about energy density and driving mileage makes ternary materials more popular. However, the residual alkali content in ternary materials seriously affects the use of lithium batteries. Excessive residual alkali content will cause serious gas production in ternary lithium batteries and also cause higher internal resistance. Summary of the invention

[0004] Purpose of the invention: The purpose of the present invention is to solve the problem in the prior art that the residual alkali content of ternary materials is high, which leads to high internal resistance of ternary lithium batteries, and to provide a ternary material for lithium batteries with low residual alkali content and a preparation method thereof.

[0005] Technical solution: A method for preparing a ternary material for a lithium battery with low residual alkali content of the present invention comprises the following steps:

[0006] S1. Mixing a nickel-cobalt-manganese ternary positive electrode material precursor and lithium carbonate in a certain proportion to form a uniformly dispersed material, wherein the chemical formula of the nickel-cobalt-manganese ternary positive electrode material precursor is Ni x Co y Mn z (OH)2, where x+y+z=1;

[0007] S2. The mixed materials in step S1 are fed into the kiln and sintered according to the intake and exhaust process in which the air intake volume, air intake pressure and kiln pressure are set to decrease in sequence from the temperature drop section, constant temperature section to the temperature rise section in the kiln;

[0008] S3. The sintered material in step S2 is crushed and mixed with additives, and then coated and sintered twice or three times to prepare a lithium battery ternary material with low residual alkali content.

[0009] Furthermore, the lithium carbonate and Ni in S1 x Co y Mn z The molar ratio of (OH)2 is Li / (Ni+Co+Mn)=1.0~1.1.

[0010] Furthermore, the amount of material fed into the kiln in S2 is 4-10 kg.

[0011] Furthermore, the furnace pressure of the kiln in the temperature-falling section is maintained at 30 to 100 Pa, the furnace pressure in the constant temperature section is maintained at 10 to 30 Pa, and the furnace pressure in the temperature-raising section is maintained at -5 to 5 Pa.

[0012] Furthermore, the air inlet pressure of the temperature-falling section of the kiln is maintained at 25-45 KPa, the air inlet pressure of the temperature-constant section is maintained at 15-20 KPa, and the air inlet pressure of the temperature-raising section is maintained at 8-12 KPa.

[0013] Furthermore, the gas flow rate is set to be set in a gradient from the temperature drop section to the temperature rise section, wherein the gas flow rate in the temperature drop section is maintained at 50-100 m / s. 3 / h, the air flow rate in the constant temperature section is maintained at 15~30m 3 / h, the air flow rate in the heating stage is maintained at 5~10m 3 / h.

[0014] Furthermore, the exhaust process of the kiln includes placing the exhaust fan of the kiln in the temperature rising section of 500-750°C; the exhaust plug plate opening of the kiln temperature rising section is as follows: the plug plate opening before 450°C is 0-30%, the plug plate opening at 450-600°C is 30-50%, the plug plate opening at 600-900°C is 70-100%, and the plug plate opening after 900°C is 0-30%.

[0015] Furthermore, the kiln is a push plate furnace or a roller furnace.

[0016] Furthermore, the temperature-falling section, constant temperature section and temperature-rising section of the kiln are all provided with furnace pressure gauges.

[0017] Furthermore, a low residual alkali lithium battery ternary material prepared using the above preparation method is provided.

[0018] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages: 1. By reducing the air intake volume, air intake pressure and furnace pressure from the cooling stage to the heating stage, the air flow inside the kiln can be made consistent, driving the exhaust gas to be discharged from the heating stage, avoiding the accumulation of exhaust gas inside the kiln, thereby reducing the residual alkali;

[0019] 2. The large air intake volume in the cooling section can play a positive role in reducing the material temperature, avoiding damage to the electrical components of the kiln due to excessively high temperature of the outgoing materials. On the other hand, the air intake in the cooling section enters the constant temperature section and the heating section after heat exchange, which is conducive to reducing the heating power of the constant temperature section and the heating section, and reducing production power consumption;

[0020] 3. The technical solution of the present invention is suitable for the production of large-volume pots, which is beneficial to reducing production unit consumption. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 The material prepared in Example 1 of the present invention is assembled into a half-cell and the cycle retention rate is tested. DETAILED DESCRIPTION

[0022] The technical solution of the present invention is further described below in conjunction with the accompanying drawings.

[0023] Example 1

[0024] S1. According to Ni 0.5 Co 0.2 Mn 0.3 247.3 kg of (OH)2 precursor and 104.7 kg of lithium carbonate were mixed evenly by high-speed mixer for 5 times to prepare 1760 kg of mixed material;

[0025] S2. The mixed material in step S1. is loaded into a mullite sagger at a loading amount of 7.5 kg / bowl and continuously fed into a roller furnace for sintering reaction. The sintering heating rate is 1.2 ° C / min, the constant temperature is 950 ° C, the constant temperature time is 10h, the cooling time is 5h, the air inlet pressure of the kiln cooling section, constant temperature section and heating section is 30Kpa, 15Kpa, 10Kpa respectively, the kiln pressure is 30Pa, 15Pa, 5Pa respectively, and the kiln air intake is 50m 3 / h、20m 3 / h、8m 3 / h; The exhaust process of the kiln heating stage is 0% opening before 450℃, 50% opening at 450-600℃, 100% opening at 600-850℃, 30% opening at 850-900℃, and 0% after 900℃;

[0026] S3. The sintered material in step S2. is crushed by mechanical grinding, coated with a modified additive, mixed, and subjected to secondary sintering to obtain a low residual alkali LiNi 0.5 Co 0.2 Mn 0.3 O2.

[0027] Example 2

[0028] S1. According to Ni 0.55 Co 0.15 Mn 0.3 230 kg of (OH)2 precursor and 110 kg of lithium carbonate were mixed evenly by high-speed mixer for 5 times to prepare 1700 kg of mixed material;

[0029] S2. The mixed material in step S1. is loaded into a mullite sagger at a loading amount of 6 kg / bowl and continuously fed into a roller furnace for sintering reaction. The sintering heating rate is 0.8 ° C / min, the constant temperature is 890 ° C, the constant temperature time is 8h, the cooling time is 6h, the air inlet pressure of the kiln cooling section, constant temperature section and heating section are 25Kpa, 18Kpa, 10Kpa respectively, the kiln pressure is 33Pa, 12Pa, 2Pa respectively, and the kiln air intake is 80m 3 / h、25m 3 / h、5m 3 / h; The exhaust process of the kiln heating stage is 0% opening before 450℃, 30% opening at 450-600℃, 80% opening at 600-850℃, 20% opening at 850-900℃, and 0% after 900℃;

[0030] S3. The sintered material in step S2. is crushed by mechanical grinding, coated with a modified additive, mixed, and subjected to secondary sintering to obtain a low residual alkali LiNi 0.55 Co 0.15 Mn 0.3 O2.

[0031] Example 3

[0032] S1. According to Ni 0.6 Co 0.1 Mn 0.3 221 kg of (OH)2 precursor and 113 kg of lithium carbonate were mixed evenly by high-speed mixer for 5 times to prepare 1670 kg of mixed material;

[0033] S2. The mixed material in step S1. is loaded into a mullite sagger at a loading amount of 10 kg / bowl and continuously fed into a roller furnace for sintering reaction. The sintering heating rate is 0.8 ° C / min, the constant temperature is 940 ° C, the constant temperature time is 10h, the cooling time is 5h, the air inlet pressure of the kiln cooling section, constant temperature section and heating section is 45Kpa, 20Kpa, 12Kpa respectively, the kiln pressure is 30Pa, 10Pa, -5Pa respectively, and the kiln air intake is 50m 3 / h、15m 3 / h、5m 3 / h; The exhaust process of the kiln heating stage is 30% opening before 450℃, 50% opening between 450℃ and 600℃, 100% opening between 600℃ and 850℃, 100% opening between 850℃ and 900℃, and 0% after 900℃;

[0034] S3. The sintered material in step S2. is crushed by mechanical grinding, coated with a modified additive, mixed, and subjected to secondary sintering to obtain a low residual alkali LiNi 0.6 Co 0.1 Mn0.3 O2.

[0035] Example 4

[0036] S1. According to Ni 0.4 Co 0.2 Mn 0.4 226.3 kg of (OH)2 precursor and 117.6 kg of lithium carbonate were mixed evenly by high-speed mixer for 5 times to prepare 1719.5 kg of mixed material;

[0037] S2. The mixed material in step S1. is loaded into a mullite sagger at a loading rate of 8 kg / bowl and continuously fed into a roller furnace for sintering reaction. The sintering heating rate is 0.8 ° C / min, the constant temperature is 990 ° C, the constant temperature time is 10h, the cooling time is 6h, the air inlet pressure of the kiln cooling section, constant temperature section and heating section are 25Kpa, 15Kpa, 8Kpa respectively, the kiln pressure is 30Pa, 10Pa, -5Pa respectively, and the kiln air intake is 50m 3 / h、30m 3 / h、6m 3 / h; The exhaust process of the kiln heating stage is 20% opening before 450℃, 30% opening between 450℃ and 600℃, 90% opening between 600℃ and 850℃, 70% opening between 850℃ and 900℃, and 0% after 900℃;

[0038] S3. The sintered material in step S2. is crushed by mechanical grinding, coated with a modified additive, mixed, and subjected to secondary sintering to obtain a low residual alkali LiNi 0.4 Co 0.2 Mn 0.4 O2.

[0039] Comparative Example 1

[0040] S1. According to Ni 0.5 Co 0.2 Mn 0.3 247.3 kg of (OH)2 precursor and 104.7 kg of lithium carbonate were mixed evenly by high-speed mixer for 5 times to prepare 1760 kg of mixed material;

[0041] S2. The mixed material in step S1. is loaded into a mullite sagger at a loading amount of 5.5 kg / bowl and continuously fed into a roller furnace for sintering reaction. The sintering heating rate is 1.2 ° C / min, the constant temperature is 950 ° C, the constant temperature time is 10h, the cooling time is 5h, the kiln inlet pressure is 15Kpa, the furnace pressures of the kiln cooling section, constant temperature section and heating section are 5Pa, 9Pa, -2Pa, respectively, and the kiln air intake is 40m 3 / h、12m 3 / h、15m3 / h; The exhaust process of the kiln heating stage is 30% opening before 450℃, 40% opening between 450℃ and 600℃, 50% opening between 600℃ and 850℃, 80% opening between 850℃ and 900℃, and 0% after 900℃;

[0042] S3. The sintered material in step S2. is crushed by mechanical grinding, coated with a modified additive, mixed, and subjected to secondary sintering to obtain a low residual alkali LiN i0.6 Co 0.1 Mn 0.3 O2.

[0043] Comparative Example 2

[0044] S1. According to Ni 0.5 Co 0.2 Mn 0.3 247.3 kg of (OH)2 precursor and 104.7 kg of lithium carbonate were mixed evenly by high-speed mixer for 5 times to prepare 1760 kg of mixed material;

[0045] S2. The mixed material in step S1. is loaded into a mullite sagger at a loading rate of 6.5 kg / bowl and continuously fed into a roller furnace for sintering reaction. The sintering heating rate is 1.2 ° C / min, the constant temperature is 950 ° C, the constant temperature time is 10h, the cooling time is 5h, the kiln inlet pressure is 20Kpa, the furnace pressures of the kiln cooling section, constant temperature section and heating section are 4Pa, 7Pa, 5Pa respectively, and the kiln air intake is 50m 3 / h、8m 3 / h、20m 3 / h; The exhaust process of the kiln heating stage is 20% opening before 450℃, 70% opening at 450-600℃, 40% opening at 600-850℃, 20% opening at 850-900℃, and 0% after 900℃;

[0046] S3. The sintered material in step S2. is crushed by mechanical grinding, coated with a modified additive, mixed, and subjected to secondary sintering to obtain a low residual alkali LiNi 0.4 Co 0.2 Mn 0.4 O2.

[0047] In order to verify the progressiveness of the embodiments of the present application, the following performance tests were carried out on the above-mentioned embodiments 1 to 4 and comparative examples 1 to 2: the above-mentioned materials were mixed with SP, PVDF, NMP, and carbon nanotubes in a ratio of 96:0.5:3:0.5 to prepare positive electrode sheets, and metallic lithium was used as the negative electrode sheet. Half-cells were assembled in a conventional manner, and the half-cells were tested using the Xinwei half-cell test system, with the charge and discharge test voltage being 3.0 to 4.5V.

[0048] Table 1:

[0049]

[0050]

[0051] It can be seen from the data in Table 1 that the residual alkali content of Examples 1-4 is much lower than that of Comparative Examples 1-2. At the same time, the materials prepared in Examples 1-4 are assembled into half-cells and tested, and the discharge capacity is high. The retention rate after 200 cycles at 1.0C is significantly higher than that of the comparative example. It can be seen that the lithium battery ternary material prepared by the preparation method of the present invention can effectively reduce the residual alkali content, and the material prepared by this method is used to prepare a battery, and the battery performance is higher.

[0052] The above are only specific application examples of the present invention and do not constitute any limitation on the protection scope of the present invention. Any technical solution formed by equivalent transformation or equivalent replacement shall fall within the protection scope of the present invention.

Claims

1. A method for preparing a ternary material for a lithium battery with low residual alkali content, characterized in that: The following steps are involved: S1. Mixing a nickel-cobalt-manganese ternary positive electrode material precursor and lithium carbonate in a certain proportion to form a uniformly dispersed material, wherein the chemical formula of the nickel-cobalt-manganese ternary positive electrode material precursor is Ni x Co y Mn z (OH)2, where x+y+z=1; S2. The mixed materials in step S1 are fed into the kiln and sintered according to the intake and exhaust process in which the air intake volume, air intake pressure and kiln pressure are set to decrease in sequence from the temperature drop section, constant temperature section to the temperature rise section in the kiln; S3. The sintered material in step S2 is crushed and mixed with additives, and then coated and sintered twice or three times to prepare a lithium battery ternary material with low residual alkali content.

2. The method for preparing a ternary material for a lithium battery with low residual alkali content according to claim 1, characterized in that: The lithium carbonate and Ni in S1 x Co y The molar ratio of Mnz(OH)2 is Li / (Ni+Co+Mn)=1.0~1.

1.

3. The method for preparing a ternary material for a lithium battery with low residual alkali content according to claim 1, characterized in that: The amount of material fed into the kiln in S2 is 4-10 kg.

4. The method for preparing a ternary material for a lithium battery with low residual alkali content according to claim 1, characterized in that: The furnace pressure of the temperature-falling section of the kiln is maintained at 30-100Pa, the furnace pressure of the temperature-constant section is maintained at 10-30Pa, and the furnace pressure of the temperature-raising section is maintained at -5-5Pa.

5. The method for preparing a ternary material for a lithium battery with low residual alkali content according to claim 1, characterized in that: The air inlet pressure of the temperature-falling section of the kiln is maintained at 25-45 Kpa, the air inlet pressure of the temperature-constant section is maintained at 15-20 Kpa, and the air inlet pressure of the temperature-raising section is maintained at 8-12 Kpa.

6. The method for preparing a ternary material for a lithium battery with low residual alkali content according to claim 1, characterized in that: The gas flow rate is set to enter the temperature section in a gradient manner from the temperature reduction section to the temperature increase section, wherein the gas flow rate in the temperature reduction section is maintained at 50-100 m 3 / h, the air flow rate in the constant temperature section is maintained at 15~30m 3 / h, the air flow rate in the heating stage is maintained at 5~10m 3 / h.

7. The method for preparing a ternary material for a lithium battery with low residual alkali content according to claim 1, characterized in that: The exhaust process of the kiln includes placing the exhaust fan of the kiln in the temperature rising section of 500-750°C; the opening of the exhaust plug plate in the temperature rising section of the kiln is as follows: the plug plate opening before 450°C is 0-30%, the plug plate opening at 450-600°C is 30-50%, the plug plate opening at 600-900°C is 70-100%, and the plug plate opening after 900°C is 0-30%.

8. The method for preparing a ternary material for a lithium battery with low residual alkali content according to claim 1, characterized in that: The kiln is a push plate furnace or a roller furnace.

9. The method for preparing a ternary material for a lithium battery with low residual alkali content according to claim 9, characterized in that: The temperature-falling section, constant temperature section and temperature-rising section of the kiln are all provided with furnace pressure gauges.

10. A ternary material for lithium batteries with low residual alkali content, characterized in that: It is prepared by the preparation method according to any one of claims 1 to 9.